2020
DOI: 10.1038/s41467-020-17890-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular properties of neural progenitors in the developing mammalian hypothalamus

Abstract: The neuroendocrine hypothalamus is the central regulator of vital physiological homeostasis and behavior. However, the cellular and molecular properties of hypothalamic neural progenitors remain unexplored. Here, hypothalamic radial glial (hRG) and hypothalamic mantle zone radial glial (hmRG) cells are found to be neural progenitors in the developing mammalian hypothalamus. The hmRG cells originate from hRG cells and produce neurons. During the early development of hypothalamus, neurogenesis occurs in radial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 72 publications
6
50
0
Order By: Relevance
“…Little is known about the role of individual hypothalamic progenitor lineages in the development of hypothalamic nuclei (Zhou et al, 2020). Taking advantage of the sparse MADM labeling system for clonal lineage analysis and TF combinations for neuronal subpopulation identification, our study revealed that the pArc progenitors are multipotent and can generate highly diverse lineage types consisting of various combinations of Arc1-4 subpopulations of different numbers.…”
Section: Features and Lineage Diversity Of Individual Hypothalamic Progenitorsmentioning
confidence: 90%
“…Little is known about the role of individual hypothalamic progenitor lineages in the development of hypothalamic nuclei (Zhou et al, 2020). Taking advantage of the sparse MADM labeling system for clonal lineage analysis and TF combinations for neuronal subpopulation identification, our study revealed that the pArc progenitors are multipotent and can generate highly diverse lineage types consisting of various combinations of Arc1-4 subpopulations of different numbers.…”
Section: Features and Lineage Diversity Of Individual Hypothalamic Progenitorsmentioning
confidence: 90%
“…The availability of scRNA-Seq from early stages of mouse and human hypothalamic neurogenesis makes it possible to directly compare these chick neuronal precursor clusters to clusters previously annotated in E11-E13 mouse (Kim et al, 2020) and gestational week 10 human hypothalamus (Zhou et al, 2020). Tuberal clusters (C0, C1, and C3) closely matched mouse arcuate and ventromedial hypothalamic clusters, as well as the human tuberal hypothalamic cluster (Fig.…”
Section: Evolutionary Conservation Of Hypothalamic Neuronal Precursor Identitymentioning
confidence: 66%
“…To identify the correlation between chicken, mouse, and human, post-mitotic hypothalamic cells from HH18 and HH20 (this work), E11-E13 mouse scRNA-Seq (Kim et al, 2020), and gestational week 10 human scRNA-Seq (Zhou et al, 2020) were used. Annotation of the human scRNA-Seq dataset was based on a mouse scRNA-Seq database and as shown in the original publication.…”
Section: Scrna-seq Data Analysismentioning
confidence: 99%
“…Anthracyclines and taxanes serve as the backbone of NACT regimens and are widely used clinically in breast cancer patients [5]. It has been proved that the E2F family of transcription factor are synergistically involved in regulating cell-cycle progression [6], controlling cell proliferation, apotosis [7] and DNA repair with consequent effects on cell growth or tumor cell invasion [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%